KNOWLEDGE AFFECTING MOTHER'S BEHAVIOR IN TREATING STUNTING TODDLERS - ST. Nurul Izzah Habibarrahman; Yusriani Yusriani; Muhammad Khidri Alwi (Homes Journal = Hospital Management Studies Journal, 2023)
Stunting is short stature with a Z-score PB/U < -2SD which occurs as a result of accumulation of chronic nutritional problems. The incidence of stunting in 2018 at the Manuju Health Center was 1 child who was stunted, in 2019 there were 3 children, in 2020 it increased to 91 children, then in 2021 there were 141 children, then in 2022 there were around 102 children who were stunted per November At the moment. This study aims to determine the effect of knowledge on mothers' behavior in caring for stunted toddlers. This research uses observational research with quantitative analysis with a cross-sectional study design. The total sample in this study was 102 mothers who had stunted toddlers. Sampling was done by simple random sampling. The data source for this study was secondary data taken in January-September 2022. The data used the chi-square test with p=0.05 and confidence interval (CI)=95%. The results of the analysis of this study showed that there was a significant relationship between knowledge and stunting toddler care behavior (p = 0.000; CI = 95%). It can be concluded that knowledge influences mothers' behavior in caring for stunting toddlers.